GANGGUAN BERBAHASA PADA PENDERITA TUNA GRAHITA - Yusuf, Muhammad; Mawaddah, Alvy (Universitas Harapan Medan, 2022)
Children who suffer from brain disorders, either disorders due to medical factors or disorders due to abnormalities in brain function also pass through the language acquisition stage. KY is a teenager who has a language disorder and is declared mentally retarded. Children with mental retardation acquire language skills in essentially the same way as non- mentally retarded children. Their rate of acquiring language skills was lower than that of non-mindset children of the same mental age. In the case of Kartini, Kartini was able to pronounce the sounds [a], [c], [d], [e], [g], [h], [i], [j], [k], [l], [s], [t], [u], and [y]. There are some consonants that cannot be pronounced if the consonants are at the beginning, in the middle and at the end. For vocals [u] Kartini can pronounce it but it is not perfect. The tongue is located between the oral cavity under the palate. For consonant [i] Kartini sometimes changes it to vowel [e]. Consonants [b], [d], [m],[t] are sometimes missing. For the consonant [n] which is located at the end of the word, Kartini changes it to the sound [ŋ]. However, for the consonant [n] which is located in the middle of the word Kartini omitted it. For consonant [s] Kartini undergoes obliteration and replacement. Consonant [s] changes to consonant [c] , Consonant [s] at the end of the word changes to consonant [t].